Acylphloroglucinol derivatives with ATP citrate lyase inhibitory activities from Syzygium oblatum Wall. (July 2021) - Huang, Jin-Chang; Liu, Yi-Nan; Tao, Yun-Hua; Chen, Bai-Yu; Lei, Chun; Fu, Wei; Li, Jing-Ya; Hu, Xiao; Hou, Ai-Jun
Abstract: Nine undescribed acylphloroglucinol derivatives, oblatones A−I, along with three known ones, were isolated from Syzygium oblatum . Their structures were determined on the basis of extensive spectroscopic analysis, including NMR and MS data interpretation. Oblatones A and B possess an alkylated chromanone scaffold featuring a hemiketal moiety. Oblatones C and D are the first acylphloroglucinol derivatives with an α, β -unsaturated ketone lipid chain. Some of the isolates showed inhibitory effects on ATP citrate lyase in vitro . The binding mode of oblatone A was predicted by molecular docking. Graphical abstract: Twelve acylphloroglucinol derivatives were isolated from Syzygium oblatum, including nine undescribed ones with structural diversity. Some of the isolates showed potent inhibitory activities against ATP citrate lyase. Image 1 Highlights: Twelve acylphloroglucinol derivatives were isolated from Syzygium oblatum. Nine of the isolates with structural diversity are undescribed. Some of the isolates showed potent inhibition against ATP citrate lyase. The binding mode with ACLY was predicted by molecular docking.